"Qu'est-ce que l'économie ?" L'approche herméneutique de Robert L. Heilbroner Suivi de "Derrière le voile de l'économie" et "Vision et idéologie" de Robert L. Heilbroner - Ferraton, Cyrille (Feuillets : économie politique moderne, 2022)
Robert L. Heilbroner is the author of the bestseller The Worldly Philosophers (1953). This hugely successful book, which focuses on the ideas of the great economists (Adam Smith, Karl Marx, Joseph Schumpeter, John Maynard Keynes, etc.), has most likely contributed to obsucring his other important work on economic policy, capitalism, socialism, the environmental problem, population growth. Heilbroner has always been very critical of the direction taken by modern economists, denouncing in particular the a-historical and depoliticised nature of their work. As an alternative, he proposes a situated and historical approach that takes into account the social, political and moral dimensions of economic change. This book, which offers an analysis and translation of two unpublished texts, is an invitation to discover the ideas of Heilbroner, who was concerned about the future of modern societies and who always believed in the fruitfulness of social sciences